2016
DOI: 10.1186/s12877-016-0377-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical functioning among men and women aged 50–79 years in Germany: an analysis of National Health Interview and Examination Surveys, 1997–1999 and 2008–2011

Abstract: BackgroundThis study examines changes in physical functioning among adults aged 50-79 years in Germany based on data from two German National Health Interview and Examination Surveys conducted in 1997–1999 (GNHIES98) and 2008–2011 (DEGS1).MethodsUsing cross-sectional data from the two surveys (GNHIES98, n = 2884 and DEGS1, n = 3732), we examined changes in self-reported physical functioning scores (Short Form-36 physical functioning subscale (SF-36 PF)) by sex and age groups (50–64 and 65–79 years). Covariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
6
4
0
Order By: Relevance
“…Consistent with previous studies in middle-aged and older adults in Denmark and Russia [ 43 ], and Germany [ 44 ] using SF-36 physical functioning subscale, the results in this study also showed that women reported poorer physical function than men. The sex difference was most obvious in ALEF with a mean score difference of 4.5.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies in middle-aged and older adults in Denmark and Russia [ 43 ], and Germany [ 44 ] using SF-36 physical functioning subscale, the results in this study also showed that women reported poorer physical function than men. The sex difference was most obvious in ALEF with a mean score difference of 4.5.…”
Section: Discussionsupporting
confidence: 92%
“…The former is likely due to the older age profile of this group, as previous large studies have shown decreasing SFPF scores with increasing age, especially in the female population, which formed the majority of our study population. 3,10 The latter may be attributed to second toe metatarsalgia. All groups demonstrated improvements at 2 years postoperatively to surpass their preoperative scores.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age varied between 36 years and 75 years old. Thirty-seven studies were conducted in HICs (5 in Australia, 2024 4 in Canada, 2528 4 in Spain, 2932 3 in Germany, 3335 3 in Portugal, 36–38 3 in the United Kingdom, 3941 3 in Hong Kong, 4244 2 in Singapore, 45,46 2 in the United States 47,48 and 1 each in Cyprus, 49 Czech Republic, 29 Denmark, 50 Estonia, 29 Finland, 30 France, 51 Hungary, 29 Latvia, 29 Poland, 30 Ireland, 52 South Korea, 53 the Netherlands, 54 Sweden 55 and Switzerland 56 ) and 35 in LMICs (9 in China, 30,5764 8 in India, 30,6571 10 in Brazil, 29,72…”
Section: Resultsmentioning
confidence: 99%